Modular Assembly of Protein Building Blocks to Create Precisely-Defined Megamolecules - Modica, Justin A. (2012)
Enzyme promoted assembly offers a simple and straightforward means to construct monodisperse molecular objects too large for classical organic synthesis and too small for top-down techniques. This communication outlines the design and construction of a heterobifunctional protein building block, HaloTag-cutinase, that reacts rapidly and selectively with an appropriately functionalized small molecule linker; and describes the step-wise combination of these building blocks to generate a 300 kDa “megamolecule” that is precisely-defined with respect to domain orientation, connectivity, and composition.